Sunlight exposure vs. vitamin D supplementation on bone homeostasis of vitamin D deficient rats. (February 2017) - Abulmeaty, Mahmoud Mustafa Ali
Summary: Background & aim of the work: Vitamin D deficiency is highly prevalent in our locality and worldwide. Two major sources of Vit D replenishment are available; sun exposure and dietary supplementation. This study compared sun exposure with vitamin D3 supplementation on restoring bone homeostasis in a vitamin D deficient (VDD) versus vitamin D sufficient (VDS) rat models. Methods: Vitamin D deficient-normocalcemic diet was used for 6 weeks to produce a group of VDD rats (n = 21), then were subdividedinto three equal subgroups: direct sunlight exposure subgroup (Sd subgroup), vitamin D3 treated subgroup (Tt subgroup), and a Control subgroup (Ct group). Normal rats (group II) (n = 14) were fed on normal vitamin D-diet for equal period and then subdivided into two equal subgroups: direct sunlight exposure subgroup (Ss subgroup), and a control (C) subgroup. For all of the subgroups, Exposures and supplementations were continued for 10 days, then the plasma 25 hydroxy vitamin D3, parathyroid hormone, calcium, phosphorus levels and alkaline phosphatase activity were estimated and femur bones were used to prepare histopathological sections. Results: The sun-exposed vitamin D deficient group showed a significant reduction of parathyroid hormone more than that in vitamin D supplemented group vs. VDD controls (67.69 ± 13.18 and 78.93 ± 8.31 vs. 86.05 ± 9.67 pg/ml, respectively ), while sun-exposed vitamin D sufficient group showed an insignificant change (15.56 ± 2.73 vs. 16.84 ± 3.16 pg/ml). Furthermore, the improvement of osteoid area and the reduction of trabecular separation in the bone sections among vitamin D deficient rats, after sunlight exposure, were better. Conclusions: Sunlight-exposure have a more positive effect on bone structure and homeostasis than vitamin D supplementation and control. This effect was more with vitamin D deficient than vitamin D sufficient rats.